Disruption of the cytoskeleton and altered lipid metabolism in Sertoli cells - Valles, Ana Sofia (2016)
Previous work demonstrated that exposures to mild hyperthermia results in altered lipid metabolism in cultured Sertoli cells (SC), as evidenced by accumulation of lipid droplets (LD), and that these changes concur with the disruption of SC cytoskeleton. To further investigate the relationship between cytoskeleton disruption and lipid perturbations, in this study SC cultures were exposed at a constant temperature to nocodazole (NCZ), an antineoplastic agent known to interfere with the polymerization of microtubules. As previously did hyperthermia, the cytoskeletal disarrangement induced by exposure to NCZ was accompanied by a significant alteration of the mitochondrial potential, an increase in triacylglycerol levels, a considerable accumulation of LD, and a functional cell impairment manifested in reduced expression of the SC-specific protein transferrin. As also seen after hyperthermia, the effects of NCZ on all these alterations were reverted after ending the exposures. The time-course of the changes suggest that the cytoskeletal disruption could be the primary cause of the SC mitochondrial alterations, which in turn may respond for the lipid metabolic alterations, suggestive of intracellular recycling of membrane lipid components. The cytoskeleton is thus functionally relevant in maintaining the viability and survival of SC during metabolically adverse or stressful situations.